Perlindungan Hukum Korban Main Hakim Sendiri sebagai Bentuk Realisasi terhadap Hak Warga Negara Indonesia - Subakdi Subakdi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
Indonesia, as a country governed by law, cannot be separated from the regulations stated in legislation and other regulations related to the fulfillment of rights and obligations. Before the law, every citizen is entitled to the same rights and obligations. In cases of criminal acts such as vigilantism, there are regulations in place for dealing with such actions. Therefore, legal protection for victims of vigilantism must also be upheld to achieve justice in the nation and the state. The author aims to write this article to assess the effectiveness of protection measures for victims and the criminal penalties for perpetrators of vigilantism. The method used in this article is a qualitative descriptive approach. The data collection technique used by the author is through literature review from previous articles. Based on the findings presented, it can be concluded that legal protection for victims of vigilantism has been regulated by law enforcement, ensuring that it is a realization of the rights of Indonesian citizens. However, even though there are laws and regulations in place, all citizens of Indonesia, both from the government and society, must continue to fulfill their rights and obligations to create welfare for the Unitary State of the Republic of Indonesia (NKRI).